Protective Role of Triacontanol (Myricyl Alcohol) Towards the Nutrients Uptake and Growth in Brassica rapa L. Under Cadmium Stress - Shakil Ahmed; Aleeza Akram; Rehana Sardar; Nasim Ahmad Yasin; Mariam Fatima; Muhammad Jabbar; Maximilian Lackner (Agronomy)
Agricultural soil contaminated with heavy metals gradually affects crop yield and its quality. Cadmium (Cd) is a heavy metal that severely affects crop yield, such as Brassica rapa L. (turnip), which is grown in arid and semiarid regions worldwide. It also affects seed germination and seedling development. The exogenous application of triacontanol (Tria, C30H61OH) has the potential to alleviate heavy metal-induced toxic effects and promote crop yield even in contaminated environments. Therefore, in the present work, Tria was tested to lessen the toxicity of Cd to turnip plants. The current study aimed to determine how seed priming and foliar application of Tria (10 and 20 ppm) influence the morphophysiological and yield characteristics of turnip plants under Cd-induced growth inhibition. Cd reduced turnip growth by affecting its morphology, biomass, and yield parameters. On the other hand, Tria at 20 ppm via SP+FS (seed priming + foliar spray) enhanced plant growth by increasing its root and leaf fresh weight by 80 and 54%, Chl a (59%), Chl b (27%), phenolic content (39%), and mineral contents of Mg (60%) and K (39%) compared with those in the plants treated with only Cd. DPPH (2,2-diphenyl-1-picrylhydrazyl) activity was enhanced by up to 48% and ascorbic acid content by up to 96% in Cd-treated plants. These findings suggest that Tria application via both methods improved turnip yield by increasing tolerance to Cd toxicity. Therefore, this study paves the way for further exploration into a very cheap and economical way of enhancing crop production against Cd stress for farmers.